EVALUATING THE IMPACT OF ENGLISH FOR SPECIFIC PURPOSES (ESP) PROGRAMS ON ACCOUNTING STUDENTS' JOB READINESS - Prasongko, Angga; Lestari, Pritantina Yuni; Farikha, Ninik; Hamida, Ulfi Dina (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2025)
The aim of this research is to assess how effectively the English for Specific Purposes (ESP) program prepares accounting students for job opportunities. The goal of the ESP program is to provide students with the English language proficiency required in the profession, particularly in the accounting industry, which frequently deals with foreign reporting and global standards. Students, lecturers, and graduates of the accounting study program were surveyed and interviewed as part of this mixed-methods study. The findings demonstrate that the ESP program improves the students' understanding of English-language accounting terminology and their abilities for professional communication in a global environment. However, the survey also found a number of obstacles, including lecturers' lack of training and time limits. These results suggest that the ESP curriculum should be updated to emphasize speaking communication skills and practical aspects, and that lecturers' training be improved in order to fulfil the needs of industry.